2004
DOI: 10.1097/01.mnm.0000134319.32279.0f
|View full text |Cite
|
Sign up to set email alerts
|

99mTc tetrofosmin scintigraphy in acute leukaemia: the relationship between marrow uptake of tetrofosmin and P-glycoprotein and chemotherapy response

Abstract: In this study, patients with acute leukaemia showed significant uptake of tetrofosmin into the bone marrow. The addition of basal and repeated 99mTc tetrofosmin scintigraphy to the management protocol for leukaemia could lead to the preferential determination of responses to chemotherapy, by evaluating whole bone marrow non-invasively. This method seems promising, but it needs further support from various similar investigations comprising more patients in order to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…99m Tc is easily available and tumor imaging agents labeled by it have been developed quickly. TF is a lipophic, cationic diphosphate initially developed for myocardial imaging, and several researches have confirmed its accumulation in tumors [1][2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
“…99m Tc is easily available and tumor imaging agents labeled by it have been developed quickly. TF is a lipophic, cationic diphosphate initially developed for myocardial imaging, and several researches have confirmed its accumulation in tumors [1][2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
“…Tetrofosmin is a perfusion agent, 25 and is an indicator of cell viability. 26,27 Kresnik et al 8 reported decreased tetrofosmin uptake in patients with degenerative goiter and HT in a late scan obtained at 1 h after injection. In other study, Younes et al 25 showed that the mechanism of tetrofosmin uptake was dependent on the amount of mitochondrial proteins using cell-based systems.…”
Section: Fi Gu Rementioning
confidence: 99%
“…[31][32][33] The re are few re ports abo ut the use of Tc-99m tet ro fos min in di ag no sing apopto sis. Sü kan et al 26 sho wed that sig ni fi cantly in crea sed Tc-99m tet ro fos min up ta ke in to the bo ne mar row was well cor re la ted with CD95, an in hi bitor of apop to sis in pa ti ents with acu te le u ke mi a. Wa ka su gi et al 27 re por ted a ca se of ma lig nant pheoc hro mocy to ma that sho wed early in ten se up ta ke and im me di a te ra pid wash-out of Tc-99m tet ro fosmin. They al so cha rac te ri zed ove rex pres si on of the an ti-apop to tic mo le cu le Bcl-2 in this ca se, which was ref rac tory to I-131 MIBG the rapy.…”
Section: Fi Gu Rementioning
confidence: 99%
“…Pathologic uptake of Tc-99m tetrofosmin can occur in benign or malignant tumors and also in infectious or non-infectious diseases (Vijayakumar et al, 2005). The mechanism of uptake of Tc-99m tetrofosmin in non-cardiac lesions is not completely understood, but the size of the lesion, its mitochondrial-rich cellularity and perfusion (factors) play a significant role (Kinuya et al, 2003;Sükan et al, 2004). Over-expression of P-glycoprotein or multi-drug resistance can decrease tumor uptake and are also associated with resistance to cancer treatment.…”
Section: Incidental Pathologic Extra-cardiac Findings During Mpimentioning
confidence: 99%